1985
DOI: 10.1128/jvi.56.3.904-911.1985
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of the E2 glycoprotein of murine coronavirus: activation of cell-fusing activity of virions by trypsin and separation of two different 90K cleavage fragments

Abstract: In the murine coronavirus mouse hepatitis virus, a single glycoprotein, E2, is required both for attachment to cells and for cell fusion. Cell fusion induced by infection with mouse hepatitis virus strain A59 was inhibited by the addition of monospecific anti-E2 antibody after virus adsorption and penetration. Adsorption of concentrated coronavirions to uninfected cells did not cause cell fusiOn in the presence of cycloheximide. Thus, cell fusion was induced by E2 on the plasma membrane of infected 17 Cl I cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
168
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(177 citation statements)
references
References 47 publications
8
168
1
Order By: Relevance
“…The S protein forms the characteristic protruding spikes that are situated on the outside of the nucleocapsid and consists of two domains, S1 and S2. The S1 domain is associated with binding to host cellular receptors while the S2 mediates viral fusion and entry into the cell (Bosch et al, 2003;Sturman et al, 1985;Wicht et al, 2014). For TGEV, the S1 domain is a potent inducer of virus neutralizing antibodies, which are important for piglet protection.…”
Section: Neutralizing Antibodies Pedv Vaccines and Passive Protectiomentioning
confidence: 99%
“…The S protein forms the characteristic protruding spikes that are situated on the outside of the nucleocapsid and consists of two domains, S1 and S2. The S1 domain is associated with binding to host cellular receptors while the S2 mediates viral fusion and entry into the cell (Bosch et al, 2003;Sturman et al, 1985;Wicht et al, 2014). For TGEV, the S1 domain is a potent inducer of virus neutralizing antibodies, which are important for piglet protection.…”
Section: Neutralizing Antibodies Pedv Vaccines and Passive Protectiomentioning
confidence: 99%
“…Coronavirus S proteins are synthesized as single-chain precursors that oligomerize in the endoplasmic reticulum and are processed through the Golgi, eventually forming long, petal-shaped spikes that protrude from the virion surface (Lai and Holmes, 2001). In some coronaviruses, S is posttranslationally cleaved into two chains, known as S1 (the receptor binding protein) and S2 (the transmembrane fusion protein) (Frana et al, 1985;Sturman et al, 1985). Coronavirus S2 is functionally and structurally related to a large group of so-called class I viral fusion proteins, including those of orthomyxoviruses such as influenza virus, paramyxoviruses such as SV5, retroviruses such as HIV, and filoviruses such as Ebola virus (Earp et al, 2005;Eckert and Kim, 2001;Harrison, 2005;Weissenhorn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin-C has been shown to reduce the replication of certain viruses, including the poliovirus, rhinovirus, and human coronaviruses OC43 and 229E (Korant et al, 1986;Collins and Grubb, 1991). The cleavage of S protein has been shown to be essential for the induction of cell-to-cell fusion and coronavirus entry into cells (Sturman et al, 1985). Shirato et al (2011) reported the transmembrane type II serine protease 2 enhanced infection of PEDV in Vero cells by increasing virus release.…”
Section: Discussionmentioning
confidence: 99%